Effects of warm-up routines on postural balance: theoretical considerations and practical precautions - Paillard, T.; Maitre, J.; Noé, F. (Sports Medicine, 2025)
The effects of warm-up on neuromuscular qualities have been widely studied and are now relatively well known. Nevertheless, their influence on postural balance remains unclear, even though this quality is fundamental for sports performance and injury prevention. This narrative review therefore focuses on the effects of warm-up on postural balance in theory and highlights the precautions to be taken in practice. Warm-up does not impact postural balance similarly depending on the type of exercise (i.e., local exercise and general exercise) performed during the warm-up routine. With local exercises involving voluntary muscle action of short duration for a limited number of muscle groups, postural balance is improved immediately after the end of the warm-up routine. General exercises involving the whole body and a large number of muscle groups generate high levels of metabolic activity that can produce transient deleterious effects on postural balance and delay the beneficial effects of warm-up. When warm-up routines use a combination of general and stretching or a combination of general, local and stretching exercises, the beneficial effects of warm-up can also be delayed if the general exercise is positioned at the end of the routine. If stretching exercises are positioned at the end of the routine, there is no delay and postural balance is improved immediately after the end of the warm-up routine. Mechanistic explanations are proposed to explain how warm-up can optimize postural balance as well as practical recommendations to optimize postural balance when implementing a warm-up routine.